COUNSELING ABOUT FAMILY PLANNING COUNSELING IN PAYA BUJOK TUNONG VILLAGE, LANGSA BAROE DISTRICT, LANGSA CITY - Reva; sari Hrp, Lili Kartika; Putri, Nabila (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2022)
Counseling is a process of interaction between two or more people who build aspects of trust in a certain thing or condition. Therefore the counseling process is very dependent on the strength of communication, understanding of the material (message) and minimizing predisposing factors that can reduce the quality of the counseling. The purpose of the counseling and mentoring is to improve the welfare of mothers and children in order to realize NKKBS (Norms for Happy Small Families). Prosperous) which is the basis for realizing a prosperous society by controlling births while ensuring controlled population growth. The method used in accompanying the use of contraceptives is by means of lectures and demonstrations, which means after the community is provided with knowledge about the types, uses, side effects, advantages and disadvantages of using these contraceptives. The evaluation used is a post test which is direct and accompanied by proof of understanding in the form of direct demonstrations. Mentoring and counseling went according to plan and got results, the majority of people who played an active role in the class could mention and demonstrate the material that had been provided by the resource person. For further activities, the resource person gave suggestions that activities like this should not stop or be seasonal and should involve other family members such as parents, in-laws, husbands and people who have an influence on a mother's life.